2013
DOI: 10.26719/2013.19.7.629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community-based drowning prevention programme in northern Islamic Republic of Iran

Abstract: This study evaluated the feasibility of a drowning intervention package in northern Islamic Republic of Iran. A quasi-experimental design used pre-and post-observations among residents and tourists in waterrecreation beach areas of intervention and control regions by the Caspian Sea and in residents near the Caspian Sea coastline. The fatal drowning rate in the studied resident population in the provinces fell from 4.24 per 100 000 residents at baseline to 3.04 per 100 000 residents at endline. The risk of dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Of the prevention strategy studies, relatively few (n = 10, 11.36%) involved evaluation. Hatfield et al [ 51 ] and Houser et al [ 52 ] both evaluated rip current information campaigns, Davoudi-Kiakalayeh [ 53 ] and Moran [ 54 ] evaluated multi-year safety programs with several different components, and Wilks et al [ 55 ] and Barcala-Fuerlos et al [ 56 ] both evaluated beach safety education programs for children. Matthews et al [ 57 ] tested the effect of different variations of beach signage, Warton et al [ 58 ] conducted a global survey exploring the effect of a reality-based television show ( Bondi Rescue) on beach safety attitudes and knowledge, and McCarroll et al [ 32 ] and Van Leeuwen et al [ 59 ] conducted human trial experiments to determine which rip current escape method was most effective and thus worthy of promotion.…”
Section: Resultsmentioning
confidence: 99%
“…Of the prevention strategy studies, relatively few (n = 10, 11.36%) involved evaluation. Hatfield et al [ 51 ] and Houser et al [ 52 ] both evaluated rip current information campaigns, Davoudi-Kiakalayeh [ 53 ] and Moran [ 54 ] evaluated multi-year safety programs with several different components, and Wilks et al [ 55 ] and Barcala-Fuerlos et al [ 56 ] both evaluated beach safety education programs for children. Matthews et al [ 57 ] tested the effect of different variations of beach signage, Warton et al [ 58 ] conducted a global survey exploring the effect of a reality-based television show ( Bondi Rescue) on beach safety attitudes and knowledge, and McCarroll et al [ 32 ] and Van Leeuwen et al [ 59 ] conducted human trial experiments to determine which rip current escape method was most effective and thus worthy of promotion.…”
Section: Resultsmentioning
confidence: 99%
“…The finding from this study was consistent with the decline in the rate of drowning observed in high-income countries ( 17 , 18 ). In our study, the comparison between dome-shaped pattern in the Caspian Sea beaches ( 19 ) -where the majority of drowning took place during the warmer months-and dome- shaped pattern in the rural setting -where the majority of drowning took place in rainy season when waters level in river and lake are high- showed that the drowning rate was not related to the climate. This situation was not comparable with previous studies ( 20 - 22 ) describing that the increase or decrease in the number of deaths was related to the seasons.…”
Section: Discussionmentioning
confidence: 62%
“…The majority of these studies found an increase in knowledge of the prevention of drowning. Most studies found a reduction in the incidence of non-fatal and fatal drowning [58,67,92]. One study did not find a significant decrease in injury rates (11.1% to 11.0%), but did find a positive increase in knowledge following a community awareness program and education materials [59].…”
Section: Plos Onementioning
confidence: 99%
“…Reduced incidence of fatal drowning [58] Addition of barriers to unsafe water areas Decreased incidence rate of non-fatal drowning [67] Community Awareness (Encouragement)…”
Section: Elimination Of Water Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation